Methods to assess performance in elite cyclists in the field - Grappe, F. (ASPETAR Sports Medicine Journal, 2016)
During racing and training, subjective and objective methods to monitor the performance of the athlete are essential. The sRPE method to quantify training load is a simple and reliable tool for the coach. The objective measurement of power output in the field to obtain RPP permits the determination of the physical potential of an athlete and provides the possibility to analyse his performance based on previous data in-competition. Physiological measures such as the AEI can further help to fine tune performance in the field.